A systematic review on the self efficacy and the use of block based visual learning for gifted students - Ahmad, Nor Aniza; Salim, Mohd Hakimi Hafidz (Faculty of Educational Studies, 2024)
This systematic review investigates the effect of block-based visual learning on the self-efficacy of gifted students, an area of increasing relevance in contemporary educational discourse. This review synthesizes findings from three databases (Proquest, EBSCOhost, Springer LINK) of empirical studies that explore how block-based programming environments, such as Scratch and Blockly, influence the self-efficacy beliefs of gifted learners. The methodology employed includes a comprehensive search of articles, conference papers, and educational reports published between 2020 and 2024, focusing on quantitative and qualitative outcomes related to self-efficacy. Results indicate that engagement with block-based programming not only enhances technical skills but also fosters a positive self-perception among gifted students, leading to increased motivation and persistence in problem-solving tasks. Furthermore, the review highlights the importance of instructional strategies that integrate block-based programming into curricula designed for gifted education. The findings underscore the potential of visual programming as a pedagogical tool that can empower gifted learners, suggesting implications for educators and policymakers in the development of curricula that support the unique needs of this population.